Identifying draught cattle in the past: lessons from large-scale analysis of archaeological datasets - Holmes, M; Thomas, R; Hamerow, H (Elsevier, 2021)
Purpose Improve understanding of the links between biological variables (sex, body size and anatomical position) and adaptive remodelling of autopodia, and the identification of traction use in the archaeological record. Methods A modified version of the recording system for identifying draught cattle in the archaeological record (Bartosiewicz et al., 1997) was applied to a sample of 1509 bones from six sites from medieval England. Analysis focused on identifying correlations between pathological and sub-pathological changes in lower-limb bones in relation to anatomy, sex and body mass. Results A correlation between sex, body mass and lower limb bone changes was demonstrated. The need to consider anterior and posterior limb bone elements separately to maximise the potential for identifying cattle used for traction was identified. Changes in hindlimb elements were highlighted as the most useful indicator of draught use. Contribution This study provides new, detailed evidence for a previously poorly understood correlation between the effects of anatomical position, sex and body size and the nature of skeletal changes traditionally associated with draught cattle. It pulls together findings and makes comprehensive suggestions for future studies. Limitations This is a purely methodological paper. Although general results are presented, there is insufficient space to include a full case study. This will be published separately within the results of the FeedSax project. Further research Future studies into the use of cattle for draught purposes in the past should take in to account the sex and size of the animals under consideration, and analyse anterior and posterior elements separately.